Immobilization of Cadmium by Fulvic Acid-Modified Palygorskite and Plant and Soil Metabolism Responses - Jianrui Li; Yingming Xu (Toxics)
This experiment was designed to investigate the immobilization effect of fulvic acid-modified palygorskite on cadmium (Cd) and evaluate metabolism responses in plants in terms of chlorophyll, proline, and soluble protein and in soils in terms of microorganism number and enzymatic activity. The characteristics of the specific surface area and X-ray diffraction (XRD) spectra of modified palygorskite were analyzed to obtain information on the clay structure. The infrared (IR) spectrum characteristics of modified palygorskite and Cd adsorption products were analyzed to study the Cd immobilization mechanism. The modified palygorskite was hydrated magnesia aluminum silicate clay with a surface area of 50.923 m2/g and dominant mesopore distribution. The silanol group (Si-OH) and carboxyl (-COOH) present in modified palygorskite can form a complex with Cd to induce a 12.8–60.3% reduction in available Cd in soil and a 17.9–76.8% reduction in plant Cd. A 7.0–22.9% rise in chlorophyll, a 19.2–64.1% increase in proline, and a 20.1% maximum increase in soluble protein in plants were observed. A 1.45-fold maximal increase in number of bacteria, a 56.7% maximal rise in number of fungi, a 64.8–206.2% rise in dehydrogenase activity, and a 22.9-fold maximal increase in cellulase activity in the soil were obtained. Fulvic acid-modified palygorskite is a recommended Cd inactivator based on the fact that clay application reduces the ecological risk of Cd entering the food chain and stimulates plant physiological metabolism and soil biochemical activity.